Construction of single storey house in Selangor Darul Ehsan / Mohamad Amir Nasrudin Zulkepeli - Zulkepeli, Mohamad Amir Nasrudin (Universiti Teknologi MARA, Perak, 2022)
In the construction of a house, especially a single-story house, there are numerous structural parts. Footings, lintels, doors, and windows are examples of structural members. The foundation, which was placed at the lowest portion of the building structure and sat on earth below ground level, is the first structure member I'd like to discuss. Through the use of a beam and column system, all of the building's loads were shifted to the foundation. Its primary role is to uniformly and safely disperse the load to the ground. Deep foundation and shallow foundation are the two types of foundation and footing used in the construction business. Strip foundations and raft foundations are examples of shallow foundations, while pile foundations are examples of deep foundations. The foundation depth is determined by structural and soil conditions. As a result, the foundation depth for a single-story structure should be at least 1.5 meters below ground level.